2020
DOI: 10.1038/s41598-020-62184-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and antimicrobial properties differ between vaginal Lactobacillus isolates from South African women with non-optimal versus optimal microbiota

Abstract: Female genital tract (FGT) inflammation increases HIV infection susceptibility. Non-optimal cervicovaginal microbiota, characterized by depletion of Lactobacillus species and increased bacterial diversity, is associated with increased FGT cytokine production. Lactobacillus species may protect against HIV partly by reducing FGT inflammation. We isolated 80 lactobacilli from South African women with non-optimal (Nugent 4-10; n = 18) and optimal microbiota (Nugent 0-3; n = 14). Cytokine production by vaginal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 48 publications
4
43
0
Order By: Relevance
“…As previous studies have suggested that the cell wall, as well as the cell membrane, may influence the immunomodulatory properties of Lactobacillus species and that peptidoglycan may be directly immunosuppressive [ 14 , 24 ], we further investigated the relationships between Lactobacillus cell wall and membrane properties and inflammation using 64 Lactobacillus species that were isolated from the same women [ 25 ]. From these lactobacilli, the 22 isolates that induced the lowest levels of pro-inflammatory cytokine production by vaginal epithelial cells and the 22 isolates that induced the greatest cytokine responses were selected and their protein profiles evaluated using LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As previous studies have suggested that the cell wall, as well as the cell membrane, may influence the immunomodulatory properties of Lactobacillus species and that peptidoglycan may be directly immunosuppressive [ 14 , 24 ], we further investigated the relationships between Lactobacillus cell wall and membrane properties and inflammation using 64 Lactobacillus species that were isolated from the same women [ 25 ]. From these lactobacilli, the 22 isolates that induced the lowest levels of pro-inflammatory cytokine production by vaginal epithelial cells and the 22 isolates that induced the greatest cytokine responses were selected and their protein profiles evaluated using LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…The cell wall cellular component included multiple proteins involved in adhesion (adhesion exoprotein, LPXTG-motif cell wall anchor domain protein, collagen-binding protein, mannose-specific adhesin, putative mucin binding protein, sortase-anchored surface protein, and surface anchor protein). The relative abundance of this cell wall cellular component correlated positively with the level of adhesion of the isolates to vaginal epithelial cells in vitro (rho = 0.30, p = 0.0476), which in turn correlated inversely with in vitro inflammatory cytokine production by these cells in response to the isolates [ 25 ]. Importantly, the cell wall organization biological process included multiple proteins involved in peptidoglycan biosynthesis, which has the potential to dampen immune responses in a strain-dependent manner [ 14 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations